A New Image Stitching Approach for Resolution Enhancement in Camera Arrays - Baygin, Mehmet; Karakose, Mehmet (Ieee, 2015)
The major developments in digital imaging are provided thanks to the development of a digital image sensor. Camera arrays are one of the studies in this area. The camera array is formed by combining a many image sensors having the same characteristics. High resolution and high speed imaging systems can be obtained by using camera arrays. In this paper, a new feature extraction based image stitching algorithm is presented to the camera arrays. One of the advantages of the proposed algorithm, the new high resolution single image is formed by using low resolution image sensors. In the study, camera arrays are formed in 2x4 size by utilizing a different number of image sensors having the same features. The images obtained from the camera arrays is combined with a new image stitching algorithm based on the feature extraction and matching. The performance of the proposed method was tested in real time and validated with experimental results. The results of the algorithm show that the proposed approach gives faster results than a well-known image stitching algorithm.
9th International Conference on Electrical and Electronics Engineering (ELECO) -- NOV 26-28, 2015 -- Bursa, TURKEY